2021
DOI: 10.1016/j.bbrep.2021.101074
|View full text |Cite
|
Sign up to set email alerts
|

In silico assessment of EpCAM transcriptional expression and determination of the prognostic biomarker for human lung adenocarcinoma (LUAD) and lung squamous cell carcinoma (LUSC)

Abstract: Epithelial cell adhesion molecule (EpCAM) is a transmembrane glycoprotein which is involved in cell signaling, proliferation, maturation, and movement, all of which are crucial for the proper development of cells and tissues. Cleavage of the EpCAM protein leads to the up-regulation of c-myc, e-fabp, and cyclins A and E which promote tumorigenesis. EpCAM can act as potential diagnostic and prognostic biomarker for different types of cancers as it is also found to be expressed in epithelia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 62 publications
0
6
0
Order By: Relevance
“…For the immunophenotypic characterization of the primary cultures, the expression levels of some specific markers were analysed by flow cytometry. In particular: epithelial cell adhesion molecule (EpCAM), expressed in epithelial cells and correlated with tumorigenesis [ 17 ]; Cytokeratin 7 (CK7), normally produced by lung epithelial cells and commonly used as a marker for diagnosis of lung tumors [ 18 ]; CD90 (alias Thymus cell antigen 1), a well-known marker of fibroblast [ 19 , 20 ]; CD45, a ubiquitous cell surface marker of nucleated hematopoietic cells [ 21 ]. The LUAD primary cell cultures isolated exhibited a marked positivity for EpCAM and CK7/8 markers, assuring that they were constituted by cancer cells of epithelial origin with the same phenotypic features of the original tumor, as well as negligible expression of CD90 and CD45 markers, thus excluding the presence of fibroblasts and tumor-infiltrating immune cells (Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…For the immunophenotypic characterization of the primary cultures, the expression levels of some specific markers were analysed by flow cytometry. In particular: epithelial cell adhesion molecule (EpCAM), expressed in epithelial cells and correlated with tumorigenesis [ 17 ]; Cytokeratin 7 (CK7), normally produced by lung epithelial cells and commonly used as a marker for diagnosis of lung tumors [ 18 ]; CD90 (alias Thymus cell antigen 1), a well-known marker of fibroblast [ 19 , 20 ]; CD45, a ubiquitous cell surface marker of nucleated hematopoietic cells [ 21 ]. The LUAD primary cell cultures isolated exhibited a marked positivity for EpCAM and CK7/8 markers, assuring that they were constituted by cancer cells of epithelial origin with the same phenotypic features of the original tumor, as well as negligible expression of CD90 and CD45 markers, thus excluding the presence of fibroblasts and tumor-infiltrating immune cells (Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…The mRNA for epithelial cell adhesion molecule (EPCAM) 43 was upregulated on primary tumoral cells and vascularized PDTs ( Figure 3 A). Other common genes of tumor development were also maintained during the PDT formation process, such as CEACAM5 and CEACAM6.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, several studies determined that UCHL1 may be a prognostic marker and therapeutic target in NSCLC patients [ 29 , 30 ]. In the field of EPCAM, many studies indicate that it can act as a potential diagnostic and prognostic biomarker for different types of cancers, including lung cancer [ 31 , 32 , 33 ]. Moin AT et al suggested EPCAM to be a significant biomarker for human lung cancer prognosis [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the field of EPCAM, many studies indicate that it can act as a potential diagnostic and prognostic biomarker for different types of cancers, including lung cancer [ 31 , 32 , 33 ]. Moin AT et al suggested EPCAM to be a significant biomarker for human lung cancer prognosis [ 31 ]. Several studies verified that STMN1 was associated with worse survival rates for lung cancer patients [ 34 , 35 , 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%